Filtration effectiveness of N95 medical mask exposed to repeated ultraviolet germicidal irradiation room - Restuti, Ratna Dwi; Priyono, Harim; Mariska, Tara Candida; Cahyono, Arie; Bramantyo, Brastho; Soemarko, Dewi S.; Yusuf, Prasandhya Astagiri; Arman, Fitri; Prihartanto, Joedo (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground: The global Coronavirus disease (COVID-19) pandemic has created shortages of personal protective equipment (PPE) including N95 respirator medical masks. Ultraviolet Germicidal Irradiation (UVGI) is an effective way for disinfection of N95 masks before reuse. The UVGI chamber is an effective method of disinfection against SARS-CoV-2, however its effect on the N95 medical masks filtration ability is still uncertain. Purpose: To evaluate filtration effectiveness of N95 mask after repeated UV-C irradiation in the UVGI chamber. Method: This was a parallel two-group experimental study to see the effect of repeated UVGI exposure on the filtration of 2 types of N95 medical masks (type 8210 and 1860), with 25 pieces each group, using an aerosol particle counter, after 10 cycles of repeated UVGI exposure in the UVGI chamber of the ORL-HNS Department Dr. Cipto Mangunkusumo Hospital. Result: There were no significant differences in the filtration effectiveness of N95 medical masks after repeated UVGI exposure up to 10 cycles for 2 types of N95 masks and there was no significant change in the filtration ability of the N95 medical masks after repeated UVGI exposure. Conclusion: The filtration of N95 medical masks type 8210 and 1860 filtration were maintained >95% after repeated UVGI exposure with cumulative dose of 10,126-16.200 mJ/cm2 in UVGI chamber of ORL-HNS Department, Dr. Cipto Mangunkusumo Hospital. ABSTRAKLatar belakang: Pandemi Coronavirus disease 2019 (COVID-19) menyebabkan keterbatasan tersedianya alat pelindung diri (APD) termasuk masker respirator N95. Ultraviolet Germicidal Irradiation (UVGI) merupakan salah satu cara desinfeksi yang menjanjikan dan efektif, sehingga masker N95 dapat digunakan kembali. Bilik UVGI merupakan metode yang efektif dalam disinfeksi terhadap SARS-CoV-2, namun efek paparan UVGI terhadap kemampuan filtrasi masker N95 belum diketahui. Tujuan: Untuk mengevaluasi efektivitas filtrasi masker N95 setelah paparan UV-C berulang di Bilik UVGI. Metode: Penelitian ini adalah studi ekperimental dua kelompok paralel untuk melihat efek paparan UVGI berulang terhadap filtrasi 2 tipe masker N95 (tipe 8210 dan 1860) sebanyak 25 masker di setiap grup, menggunakan aerosol particle counter setelah paparan UVGI berulang sebanyak 10 siklus di Bilik UVGI Departemen THT-KL RSCM. Hasil: Tidak didapatkan perbedaan bermakna pada masker N95 pasca-paparan UVGI berulang sebanyak 10 siklus dengan rerata filtrasi pada 2 tipe masker, serta tidak terdapat perubahan signifikan kemampuan filtrasi masker N95 pasca-paparan UVGI berulang. Kesimpulan: Filtrasi masker N95 pada penelitian ini dapat dipertahankan 95% pasca-paparan UVGI berulang hingga dosis kumulatif 10.126˗16.200 mJ/cm2 di bilik UVGI Departemen THT-KL RSCM.